Volume 2D: Turbomachinery 2016
DOI: 10.1115/gt2016-56154
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Diffuser Stall and Unsteady Vortices in a Centrifugal Compressor With Vaned Diffuser

Abstract: The characteristics of a diffuser rotating stall and the evolution of a vortex generated on the diffuser leading edge (i.e., leading-edge vortex (LEV)) in a centrifugal compressor were investigated using experiments and numerical analyses. The experimental results showed that both impeller and diffuser rotating stalls occurred at 55 and 25 Hz during off-design flow operation. Both the stall cells existed only on the shroud side of the flow passages, which is in close proximity to the source location of the LEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As Bousquet et al accurately pointed out, the growth of the amplitude of a modal wave rotating in the vaneless space led to occurrence of the diffuser rotating stall; this was evident from the numerical analysis [11]. The authors also have reported that the unsteady behavior of the diffuser stall was influenced by the unsteady vortices at the leading edge of the diffuser vane during the off-design operation [12,13].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…As Bousquet et al accurately pointed out, the growth of the amplitude of a modal wave rotating in the vaneless space led to occurrence of the diffuser rotating stall; this was evident from the numerical analysis [11]. The authors also have reported that the unsteady behavior of the diffuser stall was influenced by the unsteady vortices at the leading edge of the diffuser vane during the off-design operation [12,13].…”
Section: Introductionmentioning
confidence: 70%
“…on conditions (a) and (b). Based on the previous report [12,13], this 55 Hz pressure fluctuation was caused by the impeller rotating stall.…”
Section: Transition To the Stage Stallmentioning
confidence: 99%
“…One occurred at around 58 Hz and the other occurred at around 25-30 Hz. Based on previous report (Fujisawa et al, 2016), the unsteady phenomena at around 58 Hz were caused by a rotating stall within the impeller passages. On the other hand, the lower frequency fluctuation at around 25-30 Hz, was equivalent to 25-30% of the impeller rotating speed, and was caused by a rotating stall within the vaneless diffuser.…”
Section: Compressor Performance and Stall Characteristicsmentioning
confidence: 84%
“…Vortex I is clockwise; it is affected by the tornado-like vortex and impacts the diffuser suction surface. Vortex B is counterclockwise; it rotates towards the pressure surface of the adjacent diffuser vane, blocks the mainstream in the diffuser passage, leads to increased flow loss, and even causes the diffuser to stall [23]. Comparing the vortex structures at the leading edges of TVD and SVD, it can be seen that the flow in the passage of the TVD diffuser is more complicated than that in SVD.…”
Section: Investigation Of the Flow Field In The Different Diffusersmentioning
confidence: 99%